Perbandingan Penerapan Electronic Medical Record Ditinjau dari Regulasi, Integrasi Sistem, Sistem Casemix, Fokus Pengolahan Emr dan Sop di RSUD Cilacap dan Hospital Sultan Abdul Aziz Shah Malaysia - Shofiatul Ummah; Yektiningtyastuti Yektiningtyastuti; Danu Tirta Nadi; Zahrasita Nur Indira; Norizanne Binti Abd Rahim; Riskrisna Adi Pratama (Universitas Malahayati, 2026)
ABSTRACT Medical records are an essential component of healthcare services as they function to document the entire process of patient care. The development of information technology has encouraged the transformation of medical record management from manual paper-based systems to Electronic Medical Records (EMR), which are considered capable of improving service efficiency, facilitating faster access to patient information, and supporting healthcare financing and reporting systems. However, the implementation of EMR still varies across hospitals and countries due to differences in regulatory frameworks, technological infrastructure readiness, and institutional policies. This study aims to identify and compare the implementation of Electronic Medical Records (EMR) at RSUD Cilacap, Indonesia, and Hospital Sultan Abdul Aziz Shah (HSAAS), Malaysia, in terms of regulation, system integration, casemix system, EMR data processing focus, and Standard Operating Procedures (SOP). This research employed a qualitative descriptive method with a cross-sectional and comparative design. Data were collected through observation and document review as the primary sources, supported by interviews. The results show that RSUD Cilacap implements EMR based on national regulations using a one integrated platform system, integrates EMR with the INA-CBG’s casemix system, and utilizes EMR for both internal and external reporting with SOP management under the medical records unit. In contrast, HSAAS Malaysia implements EMR based on internal hospital policies using multiple platform systems, applies the MY-DRG casemix system which is not integrated with EMR, focuses EMR processing on internal reporting, and manages SOPs under the information technology unit. In conclusion, the implementation of EMR in both hospitals differs in terms of regulation, system integration, casemix system, EMR data processing focus, and Standard Operating Procedures. Keywords: Casemix, Comparative Study, Electronic Medical Record, Integrated System, Regulation. ABSTRAK Rekam medis merupakan komponen penting dalam pelayanan kesehatan karena berfungsi sebagai sarana pendokumentasian seluruh proses pelayanan pasien. Perkembangan teknologi informasi mendorong transformasi pengelolaan rekam medis dari sistem manual berbasis kertas menuju Electronic Medical Record (EMR) yang mampu meningkatkan efisiensi pelayanan, mempercepat akses informasi pasien, serta mendukung sistem pembiayaan dan pelaporan kesehatan. Namun, implementasi EMR masih menunjukkan variasi antar rumah sakit dan antar negara akibat perbedaan regulasi, kesiapan infrastruktur teknologi, serta kebijakan institusional. Penelitian ini bertujuan untuk mengetahui dan membandingkan penerapan EMR di RSUD Cilacap, Indonesia dan Hospital Sultan Abdul Aziz Shah (HSAAS) Malaysia yang ditinjau dari aspek regulasi, integrasi sistem, sistem casemix, fokus pengolahan EMR, dan Standar Operasional Prosedur (SOP). Penelitian ini menggunakan metode deskriptif kualitatif dengan rancangan cross-sectional dan desain komparatif. Data dikumpulkan melalui observasi dan studi dokumentasi sebagai sumber utama serta wawancara sebagai data pendukung. Hasil penelitian menunjukkan bahwa RSUD Cilacap menerapkan EMR berdasarkan regulasi nasional dengan sistem one integrated platform, sistem casemix INA-CBG’s yang terintegrasi dengan EMR, serta pemanfaatan EMR untuk pelaporan internal dan eksternal dengan pengelolaan SOP oleh unit rekam medis. Sementara itu, HSAAS Malaysia menerapkan EMR berdasarkan kebijakan internal rumah sakit dengan sistem multiple platform, sistem casemix MY-DRG yang belum terintegrasi dengan EMR, fokus pengolahan EMR pada pelaporan internal, serta pengelolaan SOP oleh unit teknologi informasi. Kesimpulannya, penerapan EMR di kedua rumah sakit menunjukkan perbedaan pada aspek regulasi, integrasi sistem, sistem casemix, fokus pengolahan EMR, dan SOP. Kata Kunci: Casemix, Electronic Medical Record, Integrasi Sistem, Regulasi, Studi Komparatif.